Environmental Criminology : Spatial Analysis and Regional Issues. - Leonard, Liam (Advances in sustainability and environmental justice., 2017)
Using sociological, criminological, anthropological, historical and media analysis, this multi-disciplinary volume examines local and regional issues in environmental criminology.